THE STUDENTS’ READING INTEREST IN MEDIA “LINE WEBTOON” AT ELEVENTH-GRADE OF SMA NEGERI 2 TEMBILAHAN - Wita Rela Ningsih; Agus Mustajib; Maizarah (J-Shelves of Indragiri (JSI), 2021)
This study analyzed the students’ reading interest in media LINE Webtoon. It purposes to know the students' interest in reading toward media LINE Webtoon and some factors influencing their reading interest. The research design is descriptive research that combined qualitative and quantitative approaches. It was conducted at SMA Negeri 2 Tembilahan. The researchers used the purposive sampling technique in choosing the research samples. They distributed a questionnaire to fifty eleventh-grade students. The questionnaires were distributed to know their reading interest in media LINE Webtoon to answer the first research question. In addition, to answer the second research question, the writer used an open-ended questionnaire to know the factors influencing their interest. After collecting the data, the results were transcribed. The results of this research showed that they had a high interest in reading about media LINE Webtoon. The result of the questionnaire also supported it. The percentage was 77,84%. Furthermore, the students explained that some factors that influenced their reading interest in media LINE Webtoon were: 1) lots of good and exciting stories, 2) the students liked the picture of the story of the LINE Webtoon, 3) add students English vocabulary, 4) more motivate students to learn English, 5) helps students to understand the culture and habits of American people, 6) students can learn some slang, 7) students can learn some synonyms of a word, and 8) suggested by their friend. Based on the research results, the researchers concluded that the media LINE Webtoon has a substantial positive impact on the students.